Transnational politics of the environment : the European Union and environmental policy in Central and Eastern Europe - Andonova, Liliana B. (Global environmental accords., 2004)
A study of the effect of EU membership on Central and Eastern European environmental policy and the interplay of political incentives and industry behavior that determines policy In Transnational Politics of the Environment, Liliana Andonova examines the effect of the Europen Union (EU) on the environmental policies of Bulgaria, the Czech Republic, and Poland. Compliance with EU environmental regulations is especially onerous for Central and Eastern European countries because of the costs involved and the legacy of pollution from communist-era industries. But Andonova argues that EU integration has a positive impact on environmental policies in these countries by exerting a strong influence on the environmental interests of regulated industries. With her empirical study of chemical safety and air pollution policies from 1990 to 2000, she shows that export-competitive industries such as the chemical industry that would benefit from economic integration have an incentive to adopt EU norms. By contrast, industries such as electric utilities that primarily serve the domestic market remain opposed to EU environmental standards and must be prodded by their own governments to implement environmental-protection measures. These differences in domestic interests greatly influence the course of reforms and the adoption of EU standards. Transnational Politics of the Environment challenges the current focus on intergovernmental cooperation between East and West by highlighting the roles of industries, transnational norms, and domestic institutions in promoting change in environmental regulation. It offers a generalizable framework for understanding the politics of environmental regulation in emerging market economies, and helps bridge the divide between the study of domestic and international environmental politics.